Selective exchange film closed concentrated solution based on layered double hydroxides as well as preparation method and application of selective exchange film closed concentrated solution

By using a layered bimetal hydroxide-selective exchange film sealing concentrate solution, the existing aluminum alloy anodized film sealing technology is solved, and the significant corrosion resistance and alkali resistance improvement at lower anodized film thickness are achieved, and the process is simple and environmentally friendly.

CN119736687AInactive Publication Date: 2025-04-01HANGZHOU WIN WIN TECH CO LTD

Patent Information

Application Number
CN202510247654.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-04
Publication Date
2025-04-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing aluminum alloy anodized film sealing technology has problems such as high cost, strict requirements on pure water impurities, and dry heat treatment may lead to dye decomposition, and the operation is complex, which limits its application scope.

Method used

The blocking concentrate is prepared by a specific formula and process for the sealing treatment of aluminum alloy anodized film anodic film using a layered bimetal hydroxide-selective exchange thin film sealing concentrate, including divalent metal ions, corrosion inhibitors, pH buffers and wetting agents.

Benefits of technology

The corrosion resistance of aluminum alloy anodized film is significantly improved under the condition of low anodized film thickness. The sealing film has excellent density, improves alkali resistance and corrosion resistance. At the same time, the process operation is simple, low cost, and environmentally friendly and pollution-free.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a selective exchange film sealing concentrated solution based on layered double hydroxides. The selective exchange film sealing concentrated solution comprises divalent metal ions, a corrosion inhibitor, a pH buffering agent and a wetting agent. The invention also discloses a preparation method and application of the compound. The closed thin film obtained based on the layered double-metal hydroxide selective exchange thin film closed concentrated solution has excellent compactness, double protection on the aluminum alloy anode oxide film is achieved through selective exchange of interlayer anions of the closed thin film, and the corrosion resistance of the aluminum alloy anode oxide film is improved and enhanced; and on the premise that the aluminum alloy anode oxide film is protected from being corroded, the alkali resistance of the aluminum alloy anode oxide film is improved and enhanced, and the color fixing performance of the dye is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal surface treatment, and in particular to a layered double metal hydroxide selective exchange membrane-based closed concentrated solution and a preparation method and application thereof. Background Art

[0002] Aluminum alloys are widely used in aerospace, chemical, shipbuilding and automotive industries due to their excellent characteristics such as low density, excellent mechanical properties and good machinability. In actual application, the surface of aluminum alloys is usually anodized to improve its corrosion resistance and wear resistance, and the surface is further dyed for decorative purposes. Generally speaking, the anodized film of aluminum alloys consists of an internal barrier layer and an external porous layer. The composition of the anodized film structure determines that it must be sealed later. The quality of the sealing treatment often determines the final performance and cost of the aluminum alloy.

[0003] The sealing technologies used in the existing technology are mainly divided into high-pressure steam sealing, boiling water sealing, nickel salt sealing, cold nickel fluoride sealing and hexavalent chromium sealing. With the promotion of green chemistry and the formulation of relevant laws and regulations, the sealing technology of heavy metal salts will be gradually restricted or eliminated; high-pressure steam sealing and boiling water sealing are not only costly, but also often cause the oxide film of the latter to be destroyed during actual use due to the mismatch of expansion coefficients between the sealing material and the porous structure, which ultimately affects its performance improvement or has limited improvement effect, so its application field is very limited.

[0004] Therefore, developing a low-cost aluminum alloy anodized film sealing treatment method that can significantly improve the corrosion resistance of the anodized film under the premise of lower anodized film thickness has become one of the current research hotspots in the field of aluminum alloy sealing technology.

[0005] Chinese patent CN118932455A (publication date 2024.11.12) discloses a treatment method and application for sealing the pores of anodized aluminum alloy films. The invention application utilizes the synergistic combination of water sealing treatment and dry heat treatment to achieve the purpose of reducing the admittance value of the anodized film without adding additional additives, and effectively improves and enhances the sealing quality of the anodized film, and the entire process of the method is simple to operate; but its disadvantage is that in addition to the common problems of the above-mentioned water sealing treatment, the entire process has very strict requirements on impurities in pure water; at the same time, the temperature process of dry heat treatment may cause problems such as dye decomposition in the anodizing dyeing process, which will seriously limit its application in practice.

[0006] Chinese patent CN117845306A (publication date 2024.04.09) discloses a sealing process for improving the alkali resistance of dyed aluminum alloy anodized film. The invention application uses a three-step sealing process of pre-sealing one, pre-sealing two and sealing to achieve the purpose of achieving a dyed aluminum alloy oxide film with high alkali resistance while maintaining rich colors. The disadvantage of this invention is that nickel ions are used in the pre-sealing process one, and nickel ions may still be used in the sealing process. At the same time, the three-step sealing process is complicated and cumbersome to operate, and it is not possible to use it in first-line production. Summary of the invention

[0007] The purpose of the present invention is to provide a layered double metal hydroxide selective exchange membrane-enclosed concentrated solution and a preparation method and application thereof, so as to solve the deficiencies of the prior art.

[0008] The present invention adopts the following technical solutions: A closed concentrate based on a layered double metal hydroxide selective exchange membrane, the closed concentrate comprising divalent metal ions, a corrosion inhibitor, a pH buffer and a wetting agent; The divalent metal ions include one or more of zinc ions, magnesium ions, calcium ions and manganese ions; the divalent metal ions are provided by nitrates, iodides or bromides corresponding to the metals; The corrosion inhibitor includes one or more of sodium metavanadate, sodium pyrovanadate, sodium decavanadate, sodium molybdate, sodium 2-(1,3-benzothiazole-2-thio)succinate, sodium silicate and sodium oxalate; The pH buffer comprises one or more of tetramethylammonium hydroxide, ammonium oxalate and ammonium phthalate; The wetting agent includes a quaternary ammonium salt type cationic surfactant; The divalent metal ion content is 35-70 g / l, the corrosion inhibitor content is 200-600 g / l, the pH buffer content is 15-45 g / l, the wetting agent content is 3-8 g / l, and the balance is deionized water.

[0009] The method for preparing the concentrated solution based on the layered double metal hydroxide selective exchange membrane comprises the following steps: (1) Weigh each component according to the formula and dissolve each component into a transparent solution with deionized water; (2) Adjust the pH of the divalent metal ion solution to 8.0-9.5 with aqueous ammonia and set aside; (3) Under stirring conditions, adding the corrosion inhibitor solution, the pH buffer solution, and the wetting agent solution to the divalent metal ion solution obtained in step (2) and mixing them evenly; (4) The pH of the mixed solution obtained in step (3) is adjusted to 8.0-9.5 with aqueous ammonia to obtain the closed concentrated solution.

[0010] The above-mentioned application of the layered double hydroxide selective exchange membrane sealing concentrate in the sealing of aluminum alloy anodized film.

[0011] Further, the following steps are included: (1) Degreasing and alkali etching: Place the aluminum alloy substrate in a degreasing and alkali etching solution for degreasing and alkali etching treatment, then take it out and wash it with water; (2) Deashing: Place the aluminum alloy substrate after degreasing and alkali etching into a deashing solution for deashing treatment, and then take it out for water washing; (3) Anodizing: The aluminum alloy substrate after ash removal is placed in an anodizing solution for anodizing treatment, and then taken out for washing; (4) Dyeing: Place the anodized aluminum alloy substrate into a dyeing solution for dyeing, and then take it out and wash it with water; (5) Sealing: Place the dyed aluminum alloy substrate into a sealing solution for sealing treatment, then take it out for washing and drying with a high-pressure air gun.

[0012] Furthermore, the degreasing alkali etching solution in step (1) includes 30-40 g / l ammonia water, 25-35 g / l Na 2 CO 3 15~30g / l NaHCO 3 25~40g / l NaH 2 PO 4 , 5~8g / l Tween-60, 25~35g / l Na 2 SiO 3 10~15g / l60wt%H 2 O 2 and 0.3-0.8 g / l N-acetylethoxyaniline, the balance is deionized water; during operation, the pH of the degreasing alkali etching solution is adjusted to 6.5-8.5 with ammonia water; the working temperature of the degreasing alkali etching solution is 65-75°C, and the working time is 5-10 minutes.

[0013] Furthermore, the deashing solution in step (2) comprises 65-80 ml / l 98 wt% H 2 SO 4 , the balance is deionized water; the working temperature of the deashing solution is 25-55°C, and the working time is 45-180s.

[0014] Furthermore, the anodizing solution in step (3) comprises 25-40 ml / l 98 wt% H 2 SO 4and 45-60g / l succinic acid, the balance being deionized water; the working temperature of the anodizing solution is 20-55°C, the DC power supply is 15-30V, the working time is 15-30min; the thickness of the anodized film is 5-15μm.

[0015] Furthermore, the dyeing solution in step (4) includes 1 to 25 g / l of dye, and the balance is deionized water; the working temperature of the dyeing solution is 40 to 55° C., and the working time is 10 to 25 min.

[0016] Furthermore, the sealing solution in step (5) includes 20 to 50 ml / l of the sealing concentrate described above, and the remainder is deionized water; during operation, the pH of the sealing solution is adjusted to 8.0 to 9.5 using ammonia water; the working temperature of the sealing solution is 50 to 75° C., and the working time is 30 to 55 min.

[0017] Furthermore, in step (5), the pressure of the high-pressure air gun is 1.0 to 2.5 MPa.

[0018] Beneficial effects of the present invention:

[0019] 1. The closed film prepared by the layered double hydroxide selective exchange membrane closed concentrate of the present invention has excellent compactness, and can effectively improve the corrosion resistance of the aluminum alloy anodized film even under the premise of a relatively low anodized film thickness (5 to 15 μm).

[0020] 2. The chemical formula of layered double hydroxide can be expressed by the following general chemical formula:

[0021] Among them, M 2+ With M 3+ are the divalent and trivalent metal ions in the laminate, A y- is the interlayer anion, and z is the molar ratio of the interlayer water molecules.

[0022] It is specifically composed of positively charged layers and anions embedded between the layers to balance the charge. The interaction force between the anions and the layers is a weak ionic bond or van der Waals bond, and whether the anions will be exchanged and replaced is usually determined by the strength of the interaction between the anions and the layers. The closed film prepared by the present invention based on the layered double metal hydroxide selective exchange film closed concentrate, as a film attached to the surface of the anodized film, has the physical effect of isolating the external environment from the corrosion of the aluminum alloy anodized film. At the same time, the selective exchange of anions between the layers can be used to achieve dual protection of the aluminum alloy anodized film: that is, it can not only be used to release corrosion inhibitors, but also can absorb anions (such as chloride ions Cl) in the environment that are corrosive to the aluminum alloy substrate in the aluminum alloy corrosion environment. -), so it can improve and enhance the corrosion resistance of aluminum alloy anodized film.

[0023] 3. There are divalent metal ions and trivalent metal ions in the layered double hydroxide. The present invention is based on the layered double hydroxide selective exchange membrane closed concentrated liquid with only divalent metal ions, and the trivalent metal ions are provided by the aluminum alloy substrate. That is, they need to produce a chemical reaction with the aluminum alloy substrate to enhance the bonding force.

[0024] 4. The closed concentrate based on the layered double hydroxide selective exchange membrane of the present invention is prepared in an alkaline environment. The prepared closed membrane can improve and enhance the alkali resistance of the aluminum alloy anodized film to a certain extent while protecting it from corrosion.

[0025] 5. The closed concentrate based on the layered double hydroxide selective exchange membrane of the present invention includes a quaternary ammonium salt type cationic surfactant. This type of surfactant can also play a color fixing role in the alkaline environment in which the closed concentrate of the present invention is used (the quaternary ammonium salt type cationic surfactant will produce chemical bonds or van der Waals bonds with the anodized film and the dye under alkaline conditions, so it plays a color fixing role).

[0026] 6. The present invention is based on the preparation and application of layered double metal hydroxide selective exchange membrane closed concentrate, which has the advantages of simple operation, low cost and environmental protection. DETAILED DESCRIPTION

[0027] The present invention is further explained below in conjunction with the examples. The following examples are only used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0028] The ammonia water mentioned below refers to industrial ammonia water, which is an aqueous solution containing 25wt% to 28wt% ammonia.

[0029] The crystal water contained in the following compounds is not included in the mass.

[0030] A closed concentrate based on a layered double metal hydroxide selective exchange membrane, the closed concentrate comprising divalent metal ions, a corrosion inhibitor, a pH buffer and a wetting agent; The divalent metal ions include one or more of zinc ions, magnesium ions, calcium ions and manganese ions; the divalent metal ions are provided by nitrates, iodides or bromides corresponding to the metals; The corrosion inhibitor includes one or more of sodium metavanadate, sodium pyrovanadate, sodium decavanadate, sodium molybdate, sodium 2-(1,3-benzothiazole-2-thio)succinate, sodium silicate and sodium oxalate; The pH buffer comprises one or more of tetramethylammonium hydroxide, ammonium oxalate and ammonium phthalate; The wetting agent includes a quaternary ammonium salt type cationic surfactant; The divalent metal ion content is 35-70 g / l, the corrosion inhibitor content is 200-600 g / l, the pH buffer content is 15-45 g / l, the wetting agent content is 3-8 g / l, and the balance is deionized water.

[0031] The method for preparing the concentrated solution based on the layered double metal hydroxide selective exchange membrane comprises the following steps: (1) Weigh each component according to the formula and dissolve each component into a transparent solution with deionized water; (2) Adjust the pH of the divalent metal ion solution to 8.0-9.5 with aqueous ammonia and set aside; (3) Under stirring conditions, adding the corrosion inhibitor solution, the pH buffer solution, and the wetting agent solution to the divalent metal ion solution obtained in step (2) and mixing them evenly; (4) The pH of the mixed solution obtained in step (3) is adjusted to 8.0-9.5 with aqueous ammonia to obtain the closed concentrated solution.

[0032] The application of the above-mentioned layered double metal hydroxide selective exchange membrane sealing concentrate in the sealing of aluminum alloy anodized film comprises the following steps: (1) Degreasing and alkali etching: The aluminum alloy substrate is placed in a degreasing and alkali etching solution for degreasing and alkali etching treatment, and then taken out for washing; wherein the degreasing and alkali etching solution includes 30-40 g / l ammonia water, 25-35 g / l Na 2 CO 3 15~30g / l NaHCO 3 25~40g / l NaH 2 PO 4 , 5~8g / l Tween-60, 25~35g / l Na 2 SiO 3 10~15g / l 60wt%H 2 O 2 and 0.3-0.8g / l N-acetylethoxyaniline, the balance is deionized water; during operation, the pH of the degreasing alkali etching solution is adjusted to 6.5-8.5 with ammonia water; the working temperature of the degreasing alkali etching solution is 65-75°C, and the working time is 5-10min; (2) Deashing: The aluminum alloy substrate after degreasing and alkali etching is placed in a deashing solution for deashing treatment, and then taken out for washing; wherein the deashing solution includes 65-80 ml / l 98wt% H 2 SO 4 , the balance is deionized water; the working temperature of the deashing solution is 25-55°C, and the working time is 45-180s; (3) Anodizing: The aluminum alloy substrate after ash removal is placed in an anodizing solution for anodizing treatment, and then taken out for washing; wherein the anodizing solution comprises 25-40 ml / l 98wt% H 2 SO 4 and 45-60g / l succinic acid, the balance being deionized water; the working temperature of the anodizing solution is 20-55°C, the DC power supply is 15-30V, the working time is 15-30min; the thickness of the anodized film is 5-15μm; (4) Dyeing: The anodized aluminum alloy substrate is placed in a dyeing solution for dyeing, and then taken out for washing; wherein the dyeing solution includes 1 to 25 g / l of dye, and the remainder is deionized water; the working temperature of the dyeing solution is 40 to 55°C, and the working time is 10 to 25 min; (5) Sealing: The dyed aluminum alloy substrate is placed in a sealing solution for sealing treatment, and then taken out for washing and drying with a high-pressure air gun; wherein the sealing solution includes 20 to 50 ml / l of the aforementioned sealing concentrate, and the remainder is deionized water; during operation, ammonia water is used to adjust the pH value of the sealing solution to 8.0 to 9.5; the working temperature of the sealing solution is 50 to 75°C, and the working time is 30 to 55 minutes; the pressure of the high-pressure air gun is 1.0 to 2.5 MPa.

[0033] The corrosion resistance of the parts in the following embodiments is tested with reference to the neutral salt spray test (NSS), acetic acid salt spray test (AASS), copper accelerated acetic acid salt spray test (CASS), cyclic accelerated salt spray test (CCT) and cyclic electrolyte spray drying test (prohesion) in GB / T12967.3-2022 "Test methods for anodic oxide films of aluminum and aluminum alloys and organic polymer films Part 3: Salt spray test"; the sealing quality is tested with reference to the sodium molybdate phosphate method in GB / T 8753.1-2017 "Evaluation method for sealing quality of anodic oxide films of aluminum and aluminum alloys Part 1: Acid etching weight loss method"; and the artificial sweat test is carried out with reference to QB / T 4775-2014 "Test method for artificial sweat corrosion resistance of watch shells and their accessories" (the pH of the artificial sweat is adjusted to 10.0 by adding NaOH).

[0034] The degreasing alkali etching solution in the following examples includes 40g / l ammonia water, 30g / l Na 2 CO 3 , 20g / l NaHCO 3 、38g / l NaH 2 PO 4 , 5g / l Tween-60, 30g / l Na 2 SiO 3 、15g / l 60wt%H 2 O 2and 0.5g / l N-acetylethoxyaniline, the balance is deionized water; during operation, the pH of the degreasing alkali etching solution is adjusted to 8.0 using ammonia water; the deashing solution includes 75ml / l98wt%H 2 SO 4 , the balance is deionized water; the anodizing solution includes 30ml / l 98wt%H 2 SO 4 and 55 g / l succinic acid, the balance being deionized water.

[0035] The size of the aluminum alloy substrate involved in the following embodiments is 20 mm×50 mm×1 mm.

[0036] Example 1

[0037] The sealed concentrated solution of this embodiment includes 130 g / l zinc nitrate (zinc ion content is 45 g / l), 200 g / l sodium pyrovanadate, 25 g / l ammonium oxalate and 5 g / l 2-epoxypropyl dodecyl dimethyl quaternary ammonium salt, and the balance is deionized water.

[0038] The preparation of the sealed concentrated solution in this embodiment includes the following steps: weighing the above-mentioned components according to the formula amount, and dissolving each component into a transparent solution with deionized water; adjusting the pH of the zinc nitrate solution to 8.0 with ammonia water; adding the sodium pyrovanadate solution, the ammonium oxalate solution, and the 2-epoxypropyl dodecyl dimethyl quaternary ammonium salt solution to the zinc nitrate solution under stirring conditions, and mixing them evenly; adjusting the pH of the mixed solution to 9.5 with ammonia water, thereby obtaining the sealed concentrated solution.

[0039] (1) Degreasing and alkali etching: Place the aluminum alloy substrate in a degreasing and alkali etching solution at 70°C and pH 8.0 for 5 minutes for degreasing and alkali etching treatment, then take it out and wash it with water for later use; (2) Deashing: Place the aluminum alloy substrate after degreasing and alkali etching in a 35°C deashing solution for 50 seconds for deashing, then take it out, wash it with water and set it aside; (3) Anodizing: The aluminum alloy substrate after ash removal was placed in an anodizing solution at 35°C for 25 minutes, and a DC power supply was used to apply an 18V voltage to it for anodizing treatment. The thickness of the anodized film was 12 μm, and then it was taken out for washing and standby; (4) Dyeing: The anodized aluminum alloy substrate was placed in a dyeing solution containing 3 g / l dye (ODM DYE BLACK (BK945) produced by Hangzhou Heyun Technology Co., Ltd.) at 50°C for 15 min for dyeing, and then taken out for washing and set aside; (5) Sealing: The dyed aluminum alloy substrate is placed in a sealing solution containing 30 ml / l of sealing concentrate and a pH of 8.5 at 55°C for 40 minutes for sealing treatment, and then taken out for washing with water and blow-drying with a high-pressure air gun (1.5 MPa).

[0040] Example 2

[0041] The sealed concentrated solution of this embodiment includes 130 g / l zinc nitrate (zinc ion content is 45 g / l), 200 g / l sodium decavanadate, 25 g / l ammonium oxalate and 5 g / l 2-epoxypropyl dodecyl dimethyl quaternary ammonium salt, and the balance is deionized water.

[0042] The preparation of the sealed concentrated solution in this embodiment includes the following steps: weighing the above-mentioned components according to the formula amount, and dissolving each component into a transparent solution with deionized water; adjusting the pH of the zinc nitrate solution to 8.5 with ammonia water; adding the sodium decavanadate solution, the ammonium oxalate solution, and the 2-epoxypropyl dodecyl dimethyl ammonium salt solution to the zinc nitrate solution under stirring conditions, and mixing them evenly; adjusting the pH of the mixed solution to 9.5 with ammonia water, thereby obtaining the sealed concentrated solution.

[0043] (1) Degreasing and alkali etching: Place the aluminum alloy substrate in a degreasing and alkali etching solution at 70°C and pH 8.0 for 10 minutes for degreasing and alkali etching treatment, then take it out and wash it with water for later use; (2) Deashing: Place the aluminum alloy substrate after degreasing and alkali etching in a 35°C deashing solution for 75 seconds for deashing, then take it out, wash it with water and set it aside; (3) Anodizing: The aluminum alloy substrate after ash removal was placed in an anodizing solution at 35°C for 20 minutes, and a DC power supply was used to apply an 18V voltage to it for anodizing treatment. The thickness of the anodized film was 9 μm, and then it was taken out for washing and standby; (4) Dyeing: The anodized aluminum alloy substrate was placed in a dyeing solution containing 3 g / l dye (ODM DYE RED (R110) produced by Hangzhou Heyun Technology Co., Ltd.) at 50°C for 20 min for dyeing, and then taken out for washing and set aside; (5) Sealing: The dyed aluminum alloy substrate was placed in a sealing solution containing 25 ml / l of sealing concentrate and a pH of 9.0 at 55°C for 40 min for sealing treatment, and then taken out for washing and drying with a high-pressure air gun (1.5 MPa).

[0044] Example 3

[0045] The sealed concentrated solution of this embodiment includes 184 g / l calcium nitrate (calcium ion content is 45 g / l), 200 g / l sodium metavanadate, 25 g / l ammonium oxalate and 5 g / l 2-epoxypropyl dodecyl dimethyl quaternary ammonium salt, and the balance is deionized water.

[0046] The preparation of the sealed concentrated solution in this embodiment includes the following steps: weighing the above-mentioned components according to the formula amount, and dissolving each component into a transparent solution with deionized water; adjusting the pH of the calcium nitrate solution to 8.5 with ammonia water; adding the sodium metavanadate solution, the ammonium oxalate solution, and the 2-epoxypropyl dodecyl dimethyl ammonium salt solution to the calcium nitrate solution under stirring conditions, and mixing them evenly; adjusting the pH of the mixed solution to 9.5 with ammonia water to obtain the sealed concentrated solution.

[0047] (1) Degreasing and alkali etching: Place the aluminum alloy substrate in a degreasing and alkali etching solution at 70°C and pH 8.0 for 8 minutes for degreasing and alkali etching treatment, then take it out and wash it with water for later use; (2) Deashing: Place the aluminum alloy substrate after degreasing and alkali etching in a 35°C deashing solution for 60 seconds for deashing, then take it out, wash it with water and set it aside; (3) Anodizing: The aluminum alloy substrate after ash removal was placed in an anodizing solution at 35°C for 18 minutes, and a DC power supply was used to apply a voltage of 22V to it for anodizing treatment. The thickness of the anodized film was 10 μm, and then it was taken out for washing and standby; (4) Dyeing: The anodized aluminum alloy substrate was placed in a dyeing solution containing 5 g / l dye (ODM DYE BROWN (BN613) produced by Hangzhou Heyun Technology Co., Ltd.) at 55°C for 15 min for dyeing, and then taken out for washing and standby; (5) Sealing: The dyed aluminum alloy substrate is placed in a sealing solution containing 45 ml / l of sealing concentrate and a pH of 9.0 at 60°C for 40 minutes for sealing treatment, and then taken out for washing with water and blow-drying with a high-pressure air gun (1.5 MPa).

[0048] The performance of the products obtained in each embodiment was tested, and the test results are shown in Table 1.

[0049] Table 1

[0050] The specific embodiments of the present invention are described in detail above, but they are only examples, and the present invention is not limited to the specific embodiments described above. For those skilled in the art, any equivalent modifications and substitutions made to the present invention are also within the scope of the present invention. Therefore, the equalization changes and modifications made without departing from the spirit and scope of the present invention should be included in the scope of the present invention.

Claims

1. A method for sealing a concentrated solution based on a layered double metal hydroxide selective exchange membrane, characterized in that: The closed concentrated solution comprises divalent metal ions, corrosion inhibitors, pH buffers and wetting agents; The divalent metal ions include one or more of zinc ions, magnesium ions, calcium ions and manganese ions; the divalent metal ions are provided by nitrates, iodides or bromides corresponding to the metals; The corrosion inhibitor includes one or more of sodium metavanadate, sodium pyrovanadate, sodium decavanadate, sodium molybdate, sodium 2-(1,3-benzothiazole-2-thio)succinate, sodium silicate and sodium oxalate; The pH buffer comprises one or more of tetramethylammonium hydroxide, ammonium oxalate and ammonium phthalate; The wetting agent includes a quaternary ammonium salt type cationic surfactant; The divalent metal ion content is 35-70 g / l, the corrosion inhibitor content is 200-600 g / l, the pH buffer content is 15-45 g / l, the wetting agent content is 3-8 g / l, and the balance is deionized water.

2. The method for preparing a closed concentrate based on a layered double metal hydroxide selective exchange membrane according to claim 1, characterized in that: The following steps are involved: (1) Weigh each component according to the formula and dissolve each component into a transparent solution with deionized water; (2) Adjust the pH of the divalent metal ion solution to 8.0-9.5 with aqueous ammonia and set aside; (3) Under stirring conditions, adding the corrosion inhibitor solution, the pH buffer solution, and the wetting agent solution to the divalent metal ion solution obtained in step (2) and mixing them evenly; (4) The pH of the mixed solution obtained in step (3) is adjusted to 8.0-9.5 with aqueous ammonia to obtain the closed concentrated solution.

3. Application of the layered double hydroxide selective exchange membrane sealing concentrate as described in claim 1 in sealing pores of anodized aluminum alloy films.

4. The use according to claim 3, characterized in that: The following steps are involved: (1) Degreasing and alkali etching: Place the aluminum alloy substrate in a degreasing and alkali etching solution for degreasing and alkali etching treatment, then take it out and wash it with water; (2) Deashing: Place the aluminum alloy substrate after degreasing and alkali etching into a deashing solution for deashing treatment, and then take it out for water washing; (3) Anodizing: The aluminum alloy substrate after ash removal is placed in an anodizing solution for anodizing treatment, and then taken out for washing; (4) Dyeing: Place the anodized aluminum alloy substrate into a dyeing solution for dyeing, and then take it out and wash it with water; (5) Sealing: Place the dyed aluminum alloy substrate into a sealing solution for sealing treatment, then take it out for washing and drying with a high-pressure air gun.

5. The use according to claim 4, characterized in that: The degreasing alkali etching solution in step (1) comprises 30-40 g / l ammonia water, 25-35 g / l Na2CO3, 15-30 g / l NaHCO3, 25-40 g / l NaH2PO4, 5-8 g / l Tween-60, 25-35 g / l Na2SiO3, 10-15 g / l 60 wt% H2O2 and 0.3-0.8 g / l N-acetylethoxyaniline, with the remainder being deionized water. During operation, the pH value of the degreasing alkali etching solution is adjusted to 6.5-8.5 using ammonia water. The working temperature of the degreasing alkali etching solution is 65-75°C, and the working time is 5-10 min.

6. The use according to claim 4, characterized in that: The deashing solution in step (2) includes 65-80 ml / l 98 wt% H2SO4, and the balance is deionized water; the working temperature of the deashing solution is 25-55°C, and the working time is 45-180 seconds.

7. The use according to claim 4, characterized in that: The anodizing solution in step (3) comprises 25-40 ml / l 98 wt% H2SO4 and 45-60 g / l succinic acid, with the remainder being deionized water; the working temperature of the anodizing solution is 20-55°C, the DC power supply is 15-30 V, and the working time is 15-30 min; the thickness of the anodized film is 5-15 μm.

8. The use according to claim 4, characterized in that: The dyeing solution in step (4) includes 1 to 25 g / l of dye, and the balance is deionized water; the working temperature of the dyeing solution is 40 to 55° C., and the working time is 10 to 25 min.

9. The use according to claim 4, characterized in that: The sealing solution in step (5) comprises 20-50 ml / l of the sealing concentrate according to claim 1, and the remainder is deionized water; during operation, the pH of the sealing solution is adjusted to 8.0-9.5 using ammonia water; the working temperature of the sealing solution is 50-75° C., and the working time is 30-55 min.

10. The use according to claim 4, characterized in that: In step (5), the pressure of the high-pressure air gun is 1.0 to 2.5 MPa.

Citation Information

Patent Citations

  • Hole sealing process for improving alkali resistance of dyed aluminum alloy anode oxide film

    CN117845306A

  • Treatment method and application of aluminum alloy anode oxide film hole sealing

    CN118932455A

  • Room-temperature magnetic field assisted sealing method for aluminum alloy anode oxide film

    CN102703951A

  • Method for preparing layered double hydroxide (LDH) closing film layer on surface of magnesium alloy

    CN106086992A

  • Preparation method for anti-corrosion Mg-Al LDH / MAO composite coating of aluminum alloy

    CN109853022A

Cited By

  • Self-healing sealing coating concentrated solution as well as preparation method and application thereof

    CN120758947A

  • Self-healing sealing coating concentrate, method for its production and use

    CN120758947B